2008
DOI: 10.1007/s11240-008-9352-6
|View full text |Cite
|
Sign up to set email alerts
|

Production and rooting behaviour of rolB-transgenic plants of grape rootstock ‘Richter 110’ (Vitis berlandieri × V. rupestris)

Abstract: Production and rooting behaviour of rolB-transgenic plants of grape rootstock 'Richter 110' (Vitis berlandieri 3 V. rupestris) Abstract Genetic improvement of grape rootstocks is aimed at protection against grape phylloxera and other soil-borne pests and diseases, good rooting and graft compatibility as well as adaptability to a wide range of soil and climatic conditions. Apart from the long evaluation period required, breeding is complicated by the high heterozygosity in grapes. As an alternative to tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…RT-PCR analysis revealed that neither the rolB gene nor its mRNA were detectable in the scion, indicating no translocation from the rootstock to scion. Similar results have been observed in the pear rootstock [88] and in grapes [80]. RolC gene insertion into kiwifruit ( A. deliciosa A. Chev) generated yellow leaves, stunted growth, and reduction of fruit size and flower number, thus was unsuitable for commercial uses [99].…”
Section: Application Of a Rhizogenes Rol Genes To Fruit Tree Transupporting
confidence: 66%
“…RT-PCR analysis revealed that neither the rolB gene nor its mRNA were detectable in the scion, indicating no translocation from the rootstock to scion. Similar results have been observed in the pear rootstock [88] and in grapes [80]. RolC gene insertion into kiwifruit ( A. deliciosa A. Chev) generated yellow leaves, stunted growth, and reduction of fruit size and flower number, thus was unsuitable for commercial uses [99].…”
Section: Application Of a Rhizogenes Rol Genes To Fruit Tree Transupporting
confidence: 66%
“…PPT was the most toxic agent, requiring a concentration of 5 µM to kill 100% of calli, followed by 20 µM HYG, 500 µM SPE, and 1 mM KAN. Similar concentrations have been reported to inhibit embryo regeneration of chestnut (Rothrock et al, 2007), grape (Geier et al, 2008), oil palm (Parveez et al, 1997), Eucalyptus (Sartoretto et al, 2002) and poplar (Okumura et al, 2006). The obtained lethal doses could be considered as common for several plant species, however it was very important to establish them for C. odorata because sometimes even slight variations in the physiological conditions of a particular tissue or in its the genetic background may change its susceptibility to the toxicity of a given selective agent (Duke, 1996).…”
Section: Selective Dose Determinationsupporting
confidence: 57%
“…The effect of rolB integration into plants has been extensively studied and is implicated in extensive rootinghairy roots whereby the transformed plants show profuse rooting in the absence of an external auxin supply (Geier et al 2008). rolB has been reported to enhance shoot organogenesis (Altamura 2004).…”
Section: Resultsmentioning
confidence: 99%